IVIM Imaging of Paraspinal Muscles Following Moderate and High-Intensity Exercise in Healthy Individuals - Englund, Erin K.; Berry, David B.; Behun, John J.; Ward, Samuel R.; Frank, Lawrence R.; Shahidi, Bahar (Frontiers in Rehabilitation Sciences, 2022)
Background: Quantification of the magnitude and spatial distribution of muscle blood flow changes following exercise may improve our understanding of the effectiveness of various exercise prescriptions. Intravoxel incoherent motion (IVIM) magnetic resonance imaging (MRI) is a technique that quantifies molecular diffusion and microvascular blood flow, and has recently gained momentum as a method to evaluate a muscle’s response to exercise. It has also been shown to predict responses to exercise-based physical therapy in individuals with low back pain. However, no study has evaluated the sensitivity of IVIM-MRI to exercise of varying intensity in humans. Here, we aimed to evaluate IVIM signal changes of the paraspinal muscles in response to moderate and high intensity lumbar extension exercise in healthy individuals. Methods: IVIM data were collected in 11 healthy volunteers before and immediately after a 3-minute bout of moderate and high-intensity resisted lumbar extension. IVIM data were analyzed to determine the average perfusion fraction (f), pseudo-diffusion coefficient (D*), and diffusion coefficient (D) in the bilateral paraspinal muscles. Changes in IVIM parameters were compared between the moderate and high intensity exercise bouts. Results: Exercise increased all IVIM parameters, regardless of intensity (p<0.003). Moderate intensity exercise resulted in a 11.2%, 19.6% and 3.5% increase in f, D* and D, respectively. High intensity exercise led to a similar increase in f (12.2%), but much greater changes in D* (48.6%) and D (7.9%). Conclusion: IVIM parameter increases suggest that both the moderate and high-intensity exercise conditions elicited measurable changes in blood flow (increased f and D*) and extravascular molecular diffusion rates (increased D), and that there was a dose-dependence of exercise intensity on D* and D.